Pengembangan Proyek Penguatan Profil Pelajar Pancasila (P5) sebagai Upaya Penguatan Karakter Siswa Sekolah Dasar: Implementasi dan Tantangan - Septiany, Silvia; Darmayanti, Mela; Hendriani, Ani (University of Muhammadiyah Malang, 2024)
Globalization has become one of the causes of the moral crisis among elementary school students because the information that can be accessed digitally is increasingly widespread. Therefore, it is essential to strengthen the character of elementary school students so that they do not fall into negative things. One effort that can be made is character education based on Pancasila. Through character education, students are expected to become Pancasila students, which are the students who can apply Pancasila values in their daily lives. Therefore, this research aims to determine the implementation of the Pancasila Student Profile Strengthening Project (P5) and its influence on student character. This research uses the Bibliometric analysis method and the SPAR-4-SLR procedure. They are using the Publish or Perish database and Google Scholar. Based on the 20 selected articles regarding P5, its successful implementation can develop students' positive character, such as increasing cooperation and responsibility. The obstacles experienced are inadequate facilities and infrastructure, teacher direction, and lack of funding. Efforts that can be made include providing facilities and infrastructure and cooperation between school principals, teachers, and parents. An effective strategy for implementing P5 is to optimize the planning, implementation, and evaluation stages. The benefits of implementing P5 include that character development activities focus more on determining dimensions and assessment rubrics. Recommendations are directed to future researchers to conduct research related to the implementation of P5 in connection with other elements, such as house training for teachers to understand the concept of P5.